Effect of correlated hopping on thermoelectric properties: Exact solutions for the Falicov-Kimball model - Shvaika, A.M. (Condensed Matter Physics, 2014)
The effect of correlated hopping on the charge and heat transport is investigated for the Falicov-Kimball model. An exact solutions for the electrical and thermal conductivities and thermoelectric power are obtained within the dynamical mean field theory. The temperature dependences of the transport coefficients are analysed for the particular values of correlated hopping which correspond to the significant reconstruction of the density of states and transport function. The cases with strong enhancement of thermoelectric properties are elucidated.